Outcomes of direct and indirect medical intensive care unit admissions from the emergency department of an acute care hospital: a retrospective cohort study - Molina, Joseph Antonio D (BMJ Open, 2014)
OBJECTIVES: This study aimed to determine if the risk of adverse outcomes (in-hospital and 60-day mortality, intensive care unit (ICU) and total hospital length of stay (LOS)) was greater for medical ICU (MICU) or high dependency unit (HDU) patients indirectly admitted from the emergency department (ED) than for directly admitted patients. SETTING: This study was conducted at a large public acute care hospital in Singapore. PARTICIPANTS: In this retrospective cohort study, hospital records of patients who were admitted directly from the ED, or initially admitted to the general wards from the ED and subsequently transferred to the MICU/HDU within 24 h, were reviewed. Patients were included if they were: (A) discharged from the MICU/HDU in 2009 and were admitted from the ED and (B) transferred to the MICU/HDU within 24 h of presentation at the ED. Data from 706 patients were analysed; 58.4% were men with a median age of 61 years. PRIMARY AND SECONDARY OUTCOME MEASURES: The following outcomes were compared: in-hospital mortality, 60-day mortality, LOS at the MICU/HDU, as well as total hospital LOS. RESULTS: Of the 706 patients, 491 (69.5%) were directly admitted to the MICU/HDU. After adjusting for demographics, comorbidities, interventions at the ED and clinical parameters at the ED (heart rate, respiration, oxygen saturation, mean arterial pressure), as well as the Apache II score on arrival at the MICU/HDU, indirectly admitted patients had a higher risk of in-hospital mortality (OR=3.07, 95% CI 1.39 to 6.80), death within 60 days (OR=3.09, 95% CI 1.40 to 6.83) and risk of staying >1 day at the MICU/HDU (OR=2.54, 95% CI 1.48 to 4.36). There was no significant difference in total in-hospital LOS. CONCLUSIONS: Indirectly admitted MICU/HDU patients had generally poorer outcomes. As the magnitude of effect may vary across settings, context-specific studies may be useful for improving outcomes.